Application of the Discovery Learning Model Assisted by Visual Media to Improve the Learning Outcomes of Civics Education (PKn) on the Topic of National Symbols and Their Meanings in Class III UPT SD Negeri 292 Pinrang - Rukaiyah Rukaiyah; Muhammad Idham Khalid; Rahmat Rahmat (Edumaspul: Jurnal Pendidikan, 2024)
This class action research aims to improve the learning outcomes of Civics Education of third grade students of SD Negeri 292 Pinrang through the application of the Discovery Learning model assisted by visual media on the material of State Emblems and Their Meanings. The research methodology used a class action research design with two cycles, involving 28 students as research subjects. Data collection techniques used observation, learning outcome tests, and documentation. Data analysis was done descriptively quantitatively by comparing the average value before and after the action. The research instruments were teacher and student activity observation sheets, multiple choice and description test questions, and scoring rubrics. The results showed a significant increase in student learning outcomes from cycle I to cycle II. In the initial condition, learning completeness only reached 42.8% with an average score of 68.5. After the implementation of cycle I, the completeness increased to 67.8% with an average of 75.2. In cycle II, the completeness reached 89.2% with an average of 82.7. Student learning activities also increased from the moderate category to very good. Visual media in the form of pictures, posters, and interactive videos proved effective in helping students understand the meaning and philosophy of the Garuda Pancasila state symbol. The Discovery Learning model facilitates students to discover for themselves important concepts about national identity through a guided investigation and exploration process. The conclusion of the research shows that the application of the Discovery Learning model assisted by visual media can significantly improve students' Civics learning outcomes and create more meaningful and enjoyable learning.